And Die in the West : The Story of the O.K. Corral Gunfight - Marks, Paula Mitchell 1951- (Norman [Oklahoma] University of Oklahoma Press, 1996)
"Presents the first fully detailed, objective narrative of the celebrated gunfight, of the tensions leading up to it, and the bitter, bloody events that followed. Paula Mitchell Marks places the events surrounding the gunfight against a larger backdrop of a booming Tombstone and the fluid, frontier environment of greed, factions, and violence. In the process, Marks strips away many of the myths associated with the famous gunfight and of the West in general"--Amazon.com.
Includes bibliographical references (p. 461-468) and index.
Keywords: Earp, Morgan, -- 1851-1882; Earp, Wyatt, -- 1848-1929; Holliday, John Henry, -- 1851-1887; Frontier and pioneer life -- Arizona; Violence -- History -- 19th century -- Arizona; Tombstone (Ariz.) -- History